Vowel fronting, raising, and backing in Luzon and north-central Sulawesi - Lobel, Jason William (Wacana, Journal of the Humanities of Indonesia, 2021)
This article presents an overview of four shifts – low vowel fronting, low vowel backing, back vowel fronting, and mid vowel raising – found in a number of languages on or near the Pacific coast of Luzon in the Philippines and in north- central Sulawesi in Indonesia. A more extensive illustration of low vowel fronting is given for Umiray Dumaget than has previously been made available, and a second, sporadic correspondence in Umiray Dumaget is shown to be only irregular and unconditioned. Interactions with Philippine-type morphology are also shown to result in synchronically productive alternations in Umiray Dumaget and several of the Mongondow-Gorontalo languages.